2010
DOI: 10.1007/s10165-010-0282-x
|View full text |Cite
|
Sign up to set email alerts
|

New low-field extremity MRI, compacTscan: comparison with whole-body 1.5 T conventional MRI

Abstract: Low-field extremity magnetic resonance imaging (lfMRI) is currently commercially available and has been used clinically to evaluate rheumatoid arthritis (RA). However, one disadvantage of this new modality is that the field of view (FOV) is too small to assess hand and wrist joints simultaneously. Thus, we have developed a new lfMRI system, compacTscan, with a FOV that is large enough to simultaneously assess the entire wrist to proximal interphalangeal joint area. In this work, we examined its clinical value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The advent of low-field strength (0Á2 Tesla) E-MRI machines has decreased the procedure cost and patient discomfort to a great extent. Studies that evaluated the role of E-MRI in rheumatoid arthritis have shown that they provided information on bone erosions and synovitis comparable to that of high-field MRI [6,7]. The low-field MRI unit displayed high specificity but only moderate sensitivity for detection of bone marrow oedema [8].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of low-field strength (0Á2 Tesla) E-MRI machines has decreased the procedure cost and patient discomfort to a great extent. Studies that evaluated the role of E-MRI in rheumatoid arthritis have shown that they provided information on bone erosions and synovitis comparable to that of high-field MRI [6,7]. The low-field MRI unit displayed high specificity but only moderate sensitivity for detection of bone marrow oedema [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we do not use gadolinium (Gd) enhancement images. However, we previously reported that there was excellent agreement between our MRIs and whole‐body 1.5 T‐conventional MRI that used Gd enhancement (synovitis: κ = 0.827, bone edema: κ = 0.640, bone erosion: κ = 0.833) . According to many of the previous reports of subclinical inflammation, MTX and/or other conventional synthetic disease‐modifying anti‐rheumatic drugs (csDMARDs) were given to many patients.…”
mentioning
confidence: 52%
“…Low‐field extremity MRI which we developed was used in this study. Compact MRI score (cMRIS), which is a modified Rheumatoid Arthritis MRI Score (RAMRIS) and is an easier system than RAMRIS to use for evaluating bone erosion, was used for the evaluation of MRI images .…”
mentioning
confidence: 99%
“…In the present study, we used 0.3-T compacTscan MRI machine to obtain MRI imaging, because this technology is easier to use, allows faster imaging, is cheaper, and takes less space than conventional 1.5-T MRI machine, although the quality of the diagnostic activity is not different among these two technologies [19]. Comparison of the MRI technology with that of US will allow use of MRI to obtain whole-hand imaging at once and render assessment of imaging quality independent of operator skill.…”
Section: Discussionmentioning
confidence: 99%